Investigation of optimum reclining angles for wheelchair recliners during dental treatment - Azhar, Anisah Farzana; Nordin, Nor Hidayati Diyana; Mohd, Farah Natashah; Azmi, Nur Liyana (Universitas Muhammadiyah Surakarta, 2023)
This paper discusses the development of a wheelchair recliner for dental treatment that can accommodate users of different body mass index (BMI) categories. The study aims to identify the ergonomic angle for a dental chair, design a wheelchair recliner with appropriate reclining angles, and analyse its performance using simulations and user testing with different BMI subjects. The simulation of the wheelchair recliner was performed using the Motion of Inspiration (MOI) 3D to analyse the withstanding load, including the wheelchair load and subject load (2000 N). The displacement and safety factor for the long pin of the recliner was also analysed. The study's main findings indicate that the developed wheelchair recliner can withstand a load of 2000N, which includes both the wheelchair load and the subject's load. The study tested the wheelchair recliner with three reclined angles: 40º, 45º, and 50º. It found that regardless of their BMI category, all subjects were comfortable using the wheelchair recliner at these angles during dental treatment. Overall, the study suggests that the developed wheelchair recliner has the potential to provide comfort to wheelchair users with various BMI categories during dental treatment, eliminating the need for uncomfortable transfers from the wheelchair to the dental chair.